Developing Guided Reading Guidebook through Leveled Books to Improve Reading Skills of Grade 1 Students - Alfiani, Shahriza Wahyu; Sismulyasih SB, Nugraheti (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2024)
Guidebooks for guided reading methods through tiered books have not been found in learning reading skills. Still, based on several previous studies, the impact of using guided reading methods and tiered book media is very effective in reading skills. Therefore, this study aims to develop a guidebook product for guided reading methods through tiered books to improve the reading skills of grade 1 elementary school students. This study used a Research and Development (R&D) approach using the 4D development model, focusing on the 3 stages of 4D development namely define, design, and develop. The research subjects comprised 1 grade 1 teacher and 32 grade-1 students at SD Negeri Sarirejo 1, Demak. The data collection technique used a questionnaire which was then analyzed and described to provide an overview of the feasibility and effectiveness of the guidebook. The product feasibility test was analyzed using percentages and the product effectiveness test was analyzed using the Wilcoxon Signed Rank Test, t-test, and N-Gain test. The results of the study explained that the guidebook for guided reading methods through leveled books was said to be feasible with a value of 92.4% from media experts, 92% from material experts, and 89.7% from practitioners. The results also provide an effectiveness value through a t-test with the value of the Ha t-test analysis accepted and the N-Gain obtained is 0.63. Thus, it can be explained simply that the guidebook for guided reading methods using tiered books is feasible and effective to be used by teachers to support Indonesian language learning, especially in reading skills.